Circulating microRNAs as potential markers of human drug‐induced liver injury - Starkey Lewis, Philip J.; Dear, James; Platt, Vivien; Simpson, Kenneth J.; Craig, Darren G.N.; Antoine, Daniel J.; French, Neil S.; Dhaun, Neeraj; Webb, David J.; Costello, Eithne M.; Neoptolemos, John P.; Moggs, Jonathan; et al. (Hepatology (Baltimore, Md.), 2011)
New biomarkers of liver injury are required in the clinic and in preclinical pharmaceutical evaluation. Previous studies demonstrate that two liver‐enriched microRNAs (miR‐122 and miR‐192) are promising biomarkers of acetaminophen‐induced acute liver injury (APAP‐ALI) in mice. We have examined these molecules, for the first time, in humans with APAP poisoning. Serum miR‐122 and miR‐192 were substantially higher in APAP‐ALI patients, compared to healthy controls (median ΔΔCt [25th, 75th percentile]) (miR‐122: 1,265 [491, 4,270] versus 12.1 [7.0, 26.9], P < 0.0001; miR‐192: 6.9 [2.0, 29.2] versus 0.44 [0.30, 0.69], P < 0.0001). A heart‐enriched miR‐1 showed no difference between APAP‐ALI patients and controls, whereas miR‐218 (brain‐enriched) was slightly higher in the APAP‐ALI cohort (0.17 [0.07, 0.50] versus 0.07 [0.04, 0.12]; P = 0.01). In chronic kidney disease (CKD) patients, miR‐122 and ‐192 were modestly higher, compared to controls (miR‐122: 32.0 [21.1, 40.9] versus 12.1 [7.0, 26.9], P = 0.006; miR‐192: 1.2 [0.74, 1.9] versus 0.44 [0.30, 0.69], P = 0.005), but miR‐122 and ‐192 were substantially higher in APAP‐ALI patients than CKD patients (miR‐122: P < 0.0001; miR‐192: P < 0.0004). miR‐122 correlated with peak ALT levels in the APAP‐ALI cohort (Pearson R = 0.46, P = 0.0005), but not with prothrombin time. miR‐122 was also raised alongside peak ALT levels in a group of patients with non‐APAP ALI. Day 1 serum miR‐122 levels were almost 2‐fold higher in APAP‐ALI patients who satisfied King's College Criteria (KCC), compared to those who did not satisfy KCC, although this did not reach statistical significance (P = 0.15). Conclusion: This work provides the first evidence for the potential use of miRNAs as biomarkers of human drug‐induced liver injury. (HEPATOLOGY 2011;)